Environmental reporting policy and debt maturity: perspectives from a developing country - Hussain, Hafezali Iqbal; Kamarudin, Fakarudin; Turner, Jason J.; Mohd Thas Thaker, Hassanudin; Mohamad Anwar, Nazratul Aina (Vilnius University, 2022)
Purpose – This research investigates the impact of environmental reporting policy based on evidence from levels of the debt maturity structure of non-financial firms listed on Bursa Malaysia i.e. the Malaysian Stock Exchange. In addition, further evaluation is performed on the ability of firms to adjust to target debt maturity levels based on the environmental disclosure policy. Design/methodology/approach – The research is conducted in the context of a developing country where the political and contracting costs of the economy tend to influence financial decisions. The selection of Malaysia as the focus of the research is based on it being characterised as a relationship-based economy. Therefore, incentives for environmental reporting policy would influence firms’ riskiness, perceived transparency levels as well as the ability to access capital markets. As a consequence of these characteristics, the research proposes a static and dynamic model in order to investigate the motivation for voluntary environmental disclosure based on debt maturity levels. Findings – Empirical results from modelling the determinants of debt maturity indicate that disclosure firms tend to opt for shorter debt maturity structures. Non-discloser firms’ motivation for opting for longer structures arises from potential liquidity risks. Furthermore, discloser firms are found to have lower levels of moral hazards as well as reduced potential for bankruptcy. Discloser firms’ motivation is further evidenced by the reduced potential for cash shortages highlighting lower levels of volatility. In addition, the dynamic regime switching model provides further justification for the environmental reporting policy where voluntary disclosers have enhanced ability to adjust to target debt maturity levels further validating the notion of voluntary reporting which is guided by firm riskiness and contracting costs. Originality/value – The findings from the research provide a direct measure of firms’ contracting costs based on environmental reporting policy. The measurement is based on the debt maturity structure as well as the ability to adjust to target debt maturity levels. Results take research forward, provide insights into firms’ riskiness, liquidity as well as motivation for adopting differing policies at firm levels.